Taxonomic study of the genus Pagyda Walker, 1859 (Lepidoptera: Crambidae: Pyraustinae) from China, with descriptions of two new species. (2nd January 2020) - Qi, Wanding; Li, Houhun
ABSTRACT: Ten species of the genus Pagyda Walker, 1859 from China are studied. Two species are described as new: P. recticlavata sp. nov . and P. parallelivalva sp. nov . Photographs of adults and genitalia are provided, along with a key to all the available Chinese species and a map showing the distribution of these species in China. http://www.zoobank.org/urn:lsid:zoobank.org:act:B38800E7-156E-409A-8F89-0A11765F94A9 http://www.zoobank.org/urn:lsid:zoobank.org:act:BA799084-FDFD-4EF2-8781-13F485C8CAD3